Arbitrage Asset Pricing under Exchange Risk - IKEDA, SHINSUKE (Journal of Finance, 1991)
ABSTRACT This paper extends the APT to an international setting. Specifying a linear factor return‐generating model in local currency terms, we show that the usual risk‐diversification rule in the APT does not yield a riskless portfolio unless currency fluctuations obey the same factor model as asset returns. We then consider an arbitrage portfolio whose exchange risk is hedged by foreign riskless bonds. Under the resulting no‐arbitrage conditions, the expected returns are not on the same hyperplane, unlike the closed‐economy APT, unless they are adjusted by the cost of exchange risk hedging.